A Narrow Breathing Space. The Issue of Prisoners in Bishop János Vásárhelyi’s Correspondence between 1944 and 1945 - BENKŐ, Levente (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
In his study, the author focuses on analysing how the issue of war prisoners and of Reformed civilians dragged away from their homes is presented in the correspondence of Bishop János Vásárhelyi, the leader of the Reformed Church District of Transylvania. He also discusses the steps the bishop could take to obtain the release of the captives.The author lists a number of examples illustrating the measures implemented in September 1944 at first by the Hungarian military authorities leaving northern Transylvania and then by the Romanian and Soviet military authorities marching in and whisking along Hungarian ecclesiastical personalities and also members of the congregation.One can find out from the study the efforts Bishop János Vásárhelyi made to convince the Hungarian authorities to release the members of Romanian Greek Catholic and Orthodox high clergy they had in their custody, and afterwards how he attempted to obtain the release of the Reformed Church’s clergymen, teachers, and professors and also of one of his family members imprisoned by the Romanian authorities in Romanian lagers.Furthermore, the study points out the fact that in that period many Hungarians who were transported to the Soviet Union in large prisoner trains via Kolozsvár/Cluj asked for help too, and the bishop tried to help within the narrow margins and with the few means that he had.